Synthesis and Characterization of Strontium Ferrite Nano Powder - Thirupathi1, C.; Jose1, M.; Nithiyanantham2, S. (Asian Journal of Chemistry, 2013)
Strontium ferrite powder was successfully synthesized in both water and ethylene glycol media by co-precipitate method. The phase formation is confirmed by XRD analysis. The functional groups were identified by FTIR and the surface morphology was found by SEM. The magnetic properties were determined by vibrating sample magnetometer. From the above results, it is inferred that the use of ethylene glycol as a solvent instead of water solvent has reduced the size of the crystalline powder.